Pentingnya Menanamkan Kesadaran Bela Negara Pada Era Globalisasi di SD Negeri 024 Desa Jago Bayo - Edward, Fahmi Yohari; Rohmah, Adinda Syifa’u; Padila, Julia Dwi; Begum, An Najwa Khariunnisa; Darmawan, M. Diaz Shandy; Sinambela, Alhadid Putra; Ardiansah, Reli; Rahmayanti, Dea Putri; Akbar, M. Rizky; Manik, Dina Meitamara; Masrsabella, Cendy; Siregar, Rosi L. Vini (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Globalization brings various challenges that can affect the sense of nationalism and cultural identity. Instilling awareness of state defense to every citizen, especially the current generation as heirs and successors to the continuity of the life of the nation and state is very important in order to defend the country from threats from within and from outside military and non-military. Therefore, state defense education is crucial to shape the character of students who love the country, have awareness of the nation and state, and are able to face global threats and challenges. After the socialization of state defense at SD Negeri 024 Jago Bayo Village, Lais District, North Bengkulu Regency, we saw how the students of SD Negeri 024 were very enthusiastic about the material we provided, which means that instilling awareness of state defense from an early age is very effective to implement. This state defense socialization work program is a group work program, which aims to make students at SD Negeri 024 Desa Jago Bayo as the next generation of the nation not easily influenced by outside cultures that can have an impact on the stability of the sovereignty of the Republic of Indonesia from within.